Lymphocyte Populations in the Adventitial Layer of Hydatid Cysts in Cattle: Relationship With Cyst Fertility Status and Fasciola Hepatica Co-Infection. Issue 1 (January 2020) - Jiménez, Mauricio; Stoore, Caroll; Hidalgo, Christian; Corrêa, Felipe; Hernández, Marcela; Benavides, J.; Ferreras, M. C.; Sáenz, Leonardo; Paredes, Rodolfo
Cystic echinococcosis is a worldwide zoonosis caused by the cestode Echinococcus granulosus . Two types of hydatid cysts occur in intermediate hosts: fertile cysts that generate protoscoleces from the germinal layer of the cyst, and infertile cysts that do not produce protoscoleces and are unable to continue the life cycle of the parasite. The adventitial layer, a host-derived fibrous capsule surrounding the hydatid cyst, is suggested to play an important role in local immune regulation during infection and in fertility of the cysts. Fasciola hepatica, another important parasite of cattle, induces a characteristic Th2-like immune response that could modulate the immune response against E. granulosus . Natural co-infection of both parasites is common in cattle, but no reports describe the local immune response against E. granulosus with F. hepatica infection in the same host. This study analyzed the number and distribution of T and B cells in the adventitial layer of liver and lung cysts and the relationship with cyst fertility and F. hepatica co-infection. T lymphocytes were the predominant cell type in the adventitial layer of infertile hydatid cysts and were more numerous in infertile hydatid cysts. B lymphocyte numbers were not associated with hydatid cyst fertility. Mast cells were infrequent in the adventitial layer. The number of T and B cells was not associated with F. hepatica co-infection. The present study contributes to the understanding of local immune responses in bovine cystic echinococcosis.